Interactions between vector competence to chikungunya virus and resistance to deltamethrin in Aedes aegypti laboratory lines?. Issue 4 (28th June 2022) - Wang, Lanjiao; Fontaine, Albin; Gaborit, Pascal; Guidez, Amandine; Issaly, Jean; Girod, Romain; Kazanji, Mirdad; Rousset, Dominique; Vignuzzi, Marco; Epelboin, Yanouk; Dusfour, Isabelle
Abstract: The urban mosquito species Aedes aegypti is the main vector of arboviruses worldwide. Mosquito control with insecticides is the most prevalent method for preventing transmission in the absence of effective vaccines and available treatments; however, the extensive use of insecticides has led to the development of resistance in mosquito populations throughout the world, and the number of epidemics caused by arboviruses has increased. Three mosquito lines with different resistance profiles to deltamethrin were isolated in French Guiana, including one with the I1016 knock‐down resistant allele. Significant differences were observed in the cumulative proportion of mosquitoes with a disseminated chikungunya virus infection over time across these lines. In addition, some genes related to resistance ( CYP6BB2, CYP6N12, GST2, trypsin ) were variably overexpressed in the midgut at 7 days after an infectious bloodmeal in these three lines. Our work shows that vector competence for chikungunya virus varied between Ae. aegypti laboratory lines with different deltamethrin resistance profiles. More accurate verification of the functional association between insecticide resistance and vector competence remains to be demonstrated. Abstract : IR03, IR05, and IR13 showing contrasted resistance profiles to deltamethrin ( kdr resistance and/ or metabolic resistance); High infection rates found in all lines and significant differences observed in disseminating step presenting different midgut barriers; Relative expression level of CYP6BB2, CYP6N12, GST2, trypsin varied amid the midguts of strains used. Vector competence of Aedes aegypti for chikungunya virus varied amid isofemale lines with different deltamethrin‐resistances